NTR Anna Canteens: A Boon to Urban Poor of Andhra Pradesh, India - Abraham, Dr. Mutluri (International Journal of English Literature and Social Sciences (IJELS), 2019)
Food is a basic need for every human being. Reports stated that the urban poor are deprived for the basic food and many people in urban areas are malnourished and become baggers due to hungry, poverty and lack of food. To solve this problem, Government of Andhra Pradesh has introduced NTR Anna Canteens Scheme in Andhra Pradesh in July 2018 to provide the ready food at subsidised price to the urban poor. These canteens provide the breakfast, lunch and dinner to the urban poor at its premises. It is Rs. 5/- for each meal (Breakfast Rs.5/, Lunch Rs.5/- and Dinner Rs.5/-). Urban poor have the breakfast, lunch and dinner sufficiently with Rs.15/- and do their works/jobs in Andhra Pradesh. First, in 2011, the government of Jharkhand was started the similar scheme. But after one year it was stopped due to fewer budgets. Then the former CM of Tamil Nadu Smt. Jaya Laitha was started Amma Canteen in June 2013. She continued this scheme successfully and it becomes a model for many states of India. It also became a vote bank scheme for many state governments. Government of Andhra Pradesh started 100 NTR Anna Canteens in different urban cities of Andhra Pradesh in July 2018. This scheme was handed over Akshya Patra Foundation (NGO) to implement in Andhra Pradesh. According to the officials, on an average Rs.73/- is being spent for food per head per day at the canteen. The beneficiaries pay only Rs.15/- for breakfast, lunch and dinner, while the remaining cost of Rs.58/- spent by the Government of Andhra Pradesh. The study found that this scheme is useful to the many unemployed youth, bachelor students and employees, workers in unorganised sectors, people staying in hospitals etc. People are having sufficient food. The study found that customers were highly satisfied with Anna Canteens. This scheme is indirectly helping to increases the savings of the urban poor. Reduced malnourishments and Increased health standards of urban poor and unemployed youth.